Rescue Therapy with a Proton Pump Inhibitor Plus Amoxicillin and Rifabutin for Helicobacter pylori Infection: A Systematic Review and Meta-Analysis - Xiaoqun Liu; Hui Wang; Zhifa Lv; Youhua Wang; Ben Wang; Yong Xie; Xiaojiang Zhou; Nonghua Lv (Gastroenterology Research and Practice)
Background. To conduct a systematic review and meta-analysis of clinical trials for eradication of Helicobacter pylori (H. pylori) that included a treatment arm with a proton pump inhibitor, rifabutin, and amoxicillin. Materials and Methods. We selected clinical trials that examined the efficacy of H. pylori eradication therapies and included a study arm using the test regimen from major medical literature databases and abstracts from major gastroenterology meetings. We also did subgroup and sensitivity analyses. Results. Twenty-one studies were included in systematic review. The total eradication rates of the test regimen were 70.4% by intent-to-treat (ITT) and 72.0% by per-protocol (PP) analyses. The pooled odds ratio (OR) was 0.55 using fixed effects model (P=0.283) for the test regimen versus other triple regimens. The total eradication rates were 68.4% for the test regimen and 81.9% in the control group by ITT, while the OR was 1.08 using random effects model (P=0.019). The pooled eradication rate was 66.4% for the test regimen and 67.4% for the control group by ITT. The total adverse effects incidence were 25.1% for the test regimen. Conclusions. The test regimen for H. pylori rescue therapy may be not superior to control regimens in efficacy.